Edukasi Gizi Ibu Hamil Untuk Pencegahan Stunting Di Kecamatan Mangarabombang Kabupaten Takalar - Sumarmi Sumarmi; Mantasia Mantasia; Ernawati Ernawati; Riska Nuryana (Jurnal Pengabdian Bidang Kesehatan, 2023)
Stunting is one of the health problems in Indonesia which is caused by chronic nutritional problems due to insufficient nutritional intake during pregnancy for quite a long time and due to food being provided that is not appropriate or balanced with nutritional needs during pregnancy. Providing nutritional education to pregnant women can improve the level of knowledge of pregnant women. The aim of this community service activity is to increase knowledge and understanding as well as the role of pregnant women in the stunting prevention program which is expected to directly motivate pregnant women to participate in ensuring good nutritional intake, especially during pregnancy up to the child's 1000th day of age. The method used was lectures and questions and answers to pregnant women about nutrition during pregnancy to prevent stunting. This activity was carried out in Mangarabombang Village on November 30 2023, which was attended by 15 pregnant women. The results of this activity have an impact on increasing pregnant women's understanding of nutrition during pregnancy and preventing stunting.